Performance evaluation of IEC 61850 GOOSE-based inter-substation communication for accelerated distance protection scheme - Aftab, Mohd Asim; Roostaee, Saeed; Suhail Hussain, S.M; Ali, Ikbal; Thomas, Mini S; Mehfuz, Shabana (IET generation, transmission & distribution, 2018)
Distance protection is the most widely used protection technique for transmission line protection due to its enhanced selectivity towards fault, fast response, and availability of various relay programming algorithms. However, when faults are detected in zone 2 of a relay, instantaneous tripping is not possible and are cleared after an inherent time delay. Sometimes, this increased disturbance duration may lead to system instability, power quality problems, or may result in increased plant damage. To address this issue, communication-assisted accelerated distance protection has been employed. To have this communication for tele-protection through standardised and interoperable means, an IEC 61850 GOOSE-based communication-assisted distance protection scheme is employed. This IEC 61850 GOOSE-based accelerated scheme must meet the stringent performance requirements. Thus, this study presents the experimental validation and performance evaluation of IEC 61850 GOOSE-based accelerated protection scheme by transporting GOOOSE messages through tunnelling in inter-substation for accelerated distance protection scheme. A system-in-the-loop platform has been developed to analyse the end-to-end delay performances of GOOSE messages under different WAN scenarios here. It has been found that for worst-case scenario, there is a significant operating time saving in the proposed scheme.